Corneal Fine Needle Diathermy With Adjuvant Bevacizumab to Treat Corneal Neovascularization in Children. Issue 7 (July 2015) - Elbaz, Uri; Mireskandari, Kamiar; Shen, Carl; Ali, Asim
Abstract : Purpose: To report the outcomes of corneal fine needle diathermy (FND) with adjuvant intrastromal and subconjunctival bevacizumab injection for corneal neovascularization (CN) in children. Methods: Medical records of all children who had undergone FND with adjuvant bevacizumab injection were reviewed retrospectively. Treatment efficacy was evaluated by changes in visual acuity, regression of CN, and clearing of lipid deposits with the aid of slit-lamp color images that were taken before surgical intervention and at last follow-up visit. Postoperative complications were recorded and served to assess the safety of the procedure. Results: Nine eyes of 9 patients were included in the study. The mean age of the patients was 8.4 ± 4.2 years (4–15 years) and the mean follow-up time was 18.7 ± 12.2 months (5–35 months). Three eyes had a history of herpes simplex keratitis (HSK), 3 eyes had complete corneal anesthesia, 2 eyes had CN following suture tract infection after corneal transplant for HSK scar and limbal dermoid excision, and 1 eye had blepharokeratoconjunctivitis. After treatment, 8 eyes had complete CN resolution, and 1 eye with corneal anesthesia following brain tumor resection had partial regression in vessel distribution and size. Lipid deposition clearance lagged behind CN resolution. Mean duration of CN before treatment was 15.3 ± 14.0 months (1–37 months). Mean corrected distance visual acuity before and after surgery was 0.66 ± 0.31 and 0.50 ± 0.37 logMAR, respectively ( P = 0.02). Conclusions: Corneal FND with adjuvant bevacizumab injection is effective at treating sectorial corneal vessels in children.